Weight loss and metabolic improvement in morbidly obese subjects implanted for 1 year with an endoscopic duodenal-jejunal bypass liner - Escalona, Alex; Pimentel, Fernando; Sharp, Allan; Becerra, Pablo; Slako, Milenko; Turiel, Dannae; Muñoz, Rodrigo; Bambs, Claudia; Guzmán, Sergio; Ibáñez, Luis; Gersin, Keith (Annals of surgery, 2012)
To evaluate safety, weight loss, and cardiometabolic changes in obese subjects implanted with the duodenal-jejunal bypass liner (DJBL) for 1 year. The DJBL is an endoscopic implant that mimics the duodenal-jejunal bypass component of the Roux-en-Y gastric bypass. Previous reports have shown significant weight loss and improvement in type 2 diabetes for up to 6 months. Morbidly obese subjects were enrolled in a single arm, open label, prospective trial and implanted with the DJBL. Primary endpoints included safety and weight change from baseline to week 52. Secondary endpoints included changes in waist circumference, blood pressure, lipids, glycemic control, and metabolic syndrome. The DJBL was implanted endoscopically in 39 of 42 subjects (age: 36 ± 10 years; 80% female; weight: 109 ± 18 kg; BMI: 43.7 ± 5.9 kg/m); 24 completed 52 weeks of follow-up. Three subjects could not be implanted due to short duodenal bulb. Implantation time was 24 ± 2 minutes. There were no procedure-related complications and there were 15 early endoscopic removals. In the 52-week completer population, total body weight change from baseline was -22.1 ± 2.1 kg (P < 0.0001) corresponding to 19.9 ± 1.8% of total body weight and 47.0 ± 4.4% excess of weight loss. There were also significant improvements in waist circumference, blood pressure, total and low-density lipoprotein cholesterol, triglycerides, and fasting glucose. The DJBL is safe when implanted for 1 year, and results in significant weight loss and improvements in cardiometabolic risk factors. These results suggest that this device may be suitable for the treatment of morbid obesity and its related comorbidities. This study was registered at www.clinicaltrials.gov (NCT00985491).